Tranylcypromine ('Parnate') overdose: measurement of tranylcypromine concentrations and MAO inhibitory activity and identification of amphetamines in plasma. - Youdim, M; Aronson, J; Blau, K; Green, A; Grahame-Smith, D (1979)
A case of tranylcypromine overdose is reported. Tranylcypromine, amphetamine methamphetamine and phenylethylamine were detected in the plasma by gas chromatography and their identity confirmed by mass spectrometry. The data suggested that the amphetamines were metabolic products of tranylcypromine. Platelet monoamine oxidase activity was more than 95% inhibited during the 72 h after the overdose despite complete clinical recovery by that time. The possible role of amphetamines and phenylethylamine in causing the clinical manifestations of tranylcypromine overdose is discussed.